Customer relationship management Celcom (Malaysia) Sdn Bhd - Abdul Aziz, Sharizan (2002)
Celcom (M) Sdn Bhd is a leading provider of telecommunication services. This case looks at Celcom's business issues in terms of customer satisfaction amidst a volatile industry, increasing competition and evolving market share.